A study on strength characteristics of concrete under variable temperature curing conditions in ultra-high geothermal tunnels. (30th December 2019) - Wang, Mingnian; Hu, Yunpeng; Wang, Qiling; Tian, Hongtao; Liu, Dagang
Highlights: A new concrete curing mode of variable high-temperature was proposed. Temperature and RH had diverse effects on the macro and micro properties of concrete. The significance level of temperature, humidity and coupled effect was discussed. A prediction model of strength and the optimal curing condition was confirmed. Abstract: The heat conduction of rocks and the ventilation conditions in high geothermal tunnels always result in dynamic changes of curing temperature and humidity of concrete materials, which may further significantly affect the concrete's performances. According to the field tests on both environment and concrete's temperature and humidity, a new model for concrete curing was proposed, which can really reflect the curing process of concrete in high geothermal tunnels. Based on the model, concrete specimen tests were carried out in different conditions where the initial curing temperature was set to 40 °C, 50 °C, 60 °C, 70°C and 80 °C, respectively, and the relative humidity (RH) was maintained at 25%, 55% and 95%. The results indicate that the actual high curing temperature of concrete usually decreases with time and tends to become stable 7 days after casting. Though the initial high temperature causes a rapid growth of the concrete strength at the early age, an insufficient strength over the long-term can also be leaded. While RH has a beneficial effect on the increase of initial strength and can effectively reduce the loss of long-term strength caused by the high temperature. All of the temperature, humidity and their coupling effect can influence the strength, and the influence levels follow the order: T&RH < T < RH. Finally, a new prediction model to predict the strength of concrete used in high geothermal tunnels was proposed and verified by the field tests.